Adubação fosfatada e revestimento comestível na conservação pós-colheita de batata-doce (ipomoea batatas l.) - Deus, Maria Vanessa da Costa de (2019)
Quality at harvesting time depends on several pre-harvest factors, such as soil nutrition management. Thus, this experiment aimed to evaluate the influence of phosphate fertilization on yield, quality and the effect of edible coating on postharvest conservation of sweet potatoes. Plants were cultivated in Upanema, Brazil at 0.3 x 1.0 m spacing in a soil classified as Cambisol, which presented 12.8 mg P2O5 kg-1 soil and supplemented with 40, 80, 120 or 160 kg P2O5 ha-1 as triple superphosphate. The plots were arranged in a randomized block design with four replicates. After 140 days, the roots were harvested and stored for up to 80 days (20 ± 2 ° C, 75 ± 2% RH). A root sample of each treatment was analyzed every 20 days for physicochemical evaluation. A second experiment was carried out at laboratory to evaluate the use of edible coating (3% cassava starch) in postharvest root conservation (80 days, 20 ± 2 ° C, 75 ± 2% RH) only from the plants fertilized with the standard dose, 80 kg P2O5 ha-1. Phosphate fertilization (up to 160 kg ha-1) did not influence total root productivity. The titratable acidity (TA) increased with increasing P2O5 doses, with a maximum of 0.512% at the dose of 125 kg ha-1 and the SS/AT linearly reduced with the increase in phosphorus doses. During the potato’s storage period, there was an increase in AT, total and non-reducing soluble sugars. However, the pH, ratio SS/AT, and starch content decreased. The use of edible coating maintained higher total soluble sugars and non-reducing sugars, as well as starch in sweet potato roots during storage